Pseudo-population bootstrap for design-based inference on spatial populations - Lorenzo Fattorini; Sara Franceschi; Marzia Marcheselli; Caterina Pisani; Luca Pratelli (Environmental and Ecological Statistics, 2026)

Mammals among buildings: red squirrel personality variation along an urbanization gradient - Claudia Tranquillo; Maria Vittoria Mazzamuto; Francesca Santicchia; Francesco Bisi; Damiano Preatoni; Adriano Martinoli; Martina Spada; Rosa Maria Di Biase; Sara Franceschi; Marzia Marcheselli; Caterina Pisani; Sandro Bertolino; et al. (Animal Behaviour, 2026)

Deep-seated cave inception and shallow sulfuric acid maze cave genesis in Southern Irecê Basin, São Francisco Craton (Brazil) - Philippe Audra; Luca Pisani; Marco Antonellini; Francisco Hilario R. Bezerra; Augusto S. Auler; Vincenzo La Bruna; Giovanni Bertotti; Fabrizio Balsamo; Cayo C.C. Pontes; Rebeca S. Lima; Marjan Temovski; Xianfeng Wang; et al. (Geomorphology, 2026)

New records of rarely reported species in the Mediterranean Sea (December 2025) - MARGHERITA TOMA; DARYL AGIUS; ERNESTO AZZURRO; MARZIA BO; FABIO CROCETTA; İSMAIL DAL; TOMMASO DELLI CARRI; MEHMET CENGIZ DEVAL; LORIS GALLI; ANDROMACHI GKOULIA; FABIO GRATI; DEMETRIS KOLOKOTRONIS; et al. (Mediterranean Marine Science, 2025)
New records of rarely reported species in the Mediterranean Sea (December 2025)

Hydraulic and climate controls of hypogene and epigene speleogenesis at a regional scale in northeastern Brazil - Augusto S. Auler; Philippe Audra; Jo De Waele; Rubson P. Maia; Francisco H.R. Bezerra; Xianfeng Wang; Marco Antonellini; Fabrizio Balsamo; Giovanni Bertotti; Carla Furtado; Vincenzo La Bruna; Rebeca Lima; et al. (Geomorphology, 2025)

New records of introduced species in the Mediterranean Sea (February 2025) - PERIKLIS KLEITOU; DARYL AGIUS; SENCER AKALIN; MARCO ALBANO; IZDIHAR ALI AMMAR; COŞKUN MENDERES AYDIN; ERNESTO AZZURRO; LUCIO BELLOMO; ANDREA BONIFAZI; GIOELE CAPILLO; FABIO CROCETTA; IVAN CVITKOVIĆ; et al. (Mediterranean Marine Science, 2025)
This Collective Article compiles information on nineteen (19) species recorded in seven (7) Mediterranean countries (Croatia, Cyprus, Italy, Malta, Slovenia, Syria, and Türkiye) and across four major sub-basins (Adriatic, Western, Central, and Eastern Mediterranean). The documented taxa represent eight (8) phyla: Annelida (four species), Arthropoda (three), Bryozoa (one), Chordata (two), Cnidaria (two), Mollusca (five), Chlorophyta (one), and Ochrophyta (one). Observations originated from both dedicated scientific surveys (including trawl sampling, van Veen grabs, and harbor-wall scraping) and citizen science initiatives by divers, shell collectors, and recreational fishers. Significant first records include Notomastus aberans (Slovenia), Paraprionospio coora (Italy), Polydora cornuta (Tyrrhenian Sea), Coleusia signata (Cyprus), Penaeus aztecus (Malta), Pleopis schmackeri (Syria), Pteragogus trispilus (Italy), Triacanthus biaculeatus (Türkiye), Oculina patagonica (Syria), and Watersipora subatra (Slovenia). In the Mollusca group, Conomurex persicus extends its known range westward to the Messina Strait (southern Italy), and Sepioteuthis lessoniana is recorded for the first time in Italian waters. Additional first reports for Türkiye include Alveinus miliaceus and Retusa desgenettii in the Turkish Levantine Sea. The species Uroteuthis (Photololigo) arabica represents a first record for the entire Mediterranean basin. Finally, Colpomenia peregrina (Chlorophyta) and Caulerpa taxifolia (Ochrophyta) highlight ephemeral “boom-and-bust” occurrences in Croatia, raising questions about transient invasive dynamics. These collective findings underscore the importance of coordinated monitoring efforts, inclusive of both scientific and citizen-based approaches, to better understand and manage marine biodiversity shifts in the Mediterranean.

Gypsum cave notches and their palaeoenvironmental significance: A combined morphometric study using terrestrial laser scanning, traditional cave mapping, and geomorphological observations - Jorge Sevil-Aguareles; Luca Pisani; Veronica Chiarini; Tommaso Santagata; Jo De Waele (Geomorphology, 2025)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Design-based spatial interpolation with data driven selection of the smoothing parameter - Lorenzo Fattorini; Sara Franceschi; Marzia Marcheselli; Caterina Pisani; Luca Pratelli (Environmental and Ecological Statistics, 2023)
In the inverse distance weighting interpolation the interpolated, value is a weighted mean of the sampled values, with weights decreasing with the distances. The most widely adopted class of distance functions is the class of negative powers of order $$α $$ α and the appropriate choice of the smoothing parameter $$α $$ α is a crucial issue. In this paper, we give sufficient conditions for the design-based consistency of the inverse distance weighting interpolator when $$α $$ α is selected by cross-validation techniques, and a pseudo-population bootstrap approach is introduced to estimate the accuracy of the resulting interpolator. A simulation study is performed to empirically confirm the theoritical findings and to investigate the finite-sample properties of the interpolator obtained using leave-one-out cross-validation. Moreover, a comparison with the nearest neighbor interpolator, which is the limiting case for $$α =∞ $$ α = ∞ , is performed. Finally, the estimation of the surface of the Shannon diversity index of tree diameter at breast height in the experimental watershed of Bonis forest (Southern Italy) is described.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Antiproliferative activity of three lichen species belonging to the genus Peltigera - Silvana Munzi; Doriana Triggiani; Donatella Ceccarelli; Elisa Climati; Antonio Tiezzi; Tommaso Pisani; Luca Paoli; Stefano Loppi (Plant Biosystems, 2014)

Influence of sun irradiance and water availability on lichen photosynthetic pigments during a Mediterranean summer - Luca Paoli; Tommaso Pisani; Silvana Munzi; Carlo Gaggi; Stefano Loppi (Biologia, 2010)

Biochemical evidence of a physical interaction between Sulfolobus solfataricus B-family and Y-family DNA polymerases - Mariarita De Felice; Barbara Medagli; Luca Esposito; Mariarosaria De Falco; Biagio Pucci; Mosè Rossi; Petr Grùz; Takehiko Nohmi; Francesca M. Pisani (Extremophiles, 2007)

Biochemical characterization of two Cdc6/ORC1-like proteins from the crenarchaeon Sulfolobus solfataricus - Mariarita De Felice; Luca Esposito; Mosè Rossi; Francesca M. Pisani (Extremophiles, 2006)